ANALISIS GAMBARAN RESILIENSI KARIER GURU - Diki Arip Ramadhan; Feida Noor Laila Isti'adah (Program Studi Bimbingan dan Konseling Universitas Muhammadiyah Tasikmalaya, 2021)
The purpose of this study was to find out the description of teacher career resilience in terms of gender, teaching level, employment status, income and duration of work, then program planning as a service in tertiary institutions which is pre-emptive in nature to prospective teaching staff students. This study used a quantitative descriptive method to describe the career resilience of 637 teachers. The sampling technique in this study used a random sampling technique, namely by determining the number of samples from the population at random. In general, teacher career resilience is in the high category of 32.2% (76 people), based on gender there is no significant difference, based on teaching level, employment status, income and duration of work there are significant differences. The implications of career guidance services in this study are services that develop from the four dimensions of career resilience, namely career confidence, ignoring traditional sources of career success, independence and self-acceptance to change.